Identification of a Gut Commensal That Compromises the Blood Pressure-Lowering Effect of Ester Angiotensin-Converting Enzyme Inhibitors. Issue 8 (11th May 2022) - Yang, Tao; Mei, Xue; Tackie-Yarboi, Ethel; Akere, Millicent Tambari; Kyoung, Jun; Mell, Blair; Yeo, Ji-Youn; Cheng, Xi; Zubcevic, Jasenka; Richards, Elaine M.; Pepine, Carl J.; Raizada, Mohan K.; et al.
Abstract : Background: Despite the availability of various classes of antihypertensive medications, a large proportion of hypertensive individuals remain resistant to treatments. The reason for what contributes to low efficacy of antihypertensive medications in these individuals is elusive. The knowledge that gut microbiota is involved in pathophysiology of hypertension and drug metabolism led us to hypothesize that gut microbiota catabolize antihypertensive medications and compromised their blood pressure (BP)-lowering effects. Methods and Results: To test this hypothesis, we examined the BP responses to a representative ACE (angiotensin-converting enzyme) inhibitor quinapril in spontaneously hypertensive rats (SHR) with or without antibiotics. BP-lowering effect of quinapril was more pronounced in the SHR+antibiotics, indicating that gut microbiota of SHR lowered the antihypertensive effect of quinapril. Depletion of gut microbiota in the SHR+antibiotics was associated with decreased gut microbial catabolism of quinapril as well as significant reduction in the bacterial genus Coprococcus . C. comes, an anaerobic species of Coprococcus, harbored esterase activity and catabolized the ester quinapril in vitro. Co-administration of quinapril with C. comes reduced the antihypertensive effect of quinapril in the SHR. Importantly, C. comes selectively reduced the antihypertensive effects of ester ramipril but not nonester lisinopril. Conclusions: Our study revealed a previously unrecognized mechanism by which human commensal C. comes catabolizes ester ACE inhibitors in the gut and lowers its antihypertensive effect.